Gender Equality Guarantees Women's Rights And Opportunities - Muhammadieva Oliya Narzullaevna; Niyozova Marjona (Periodica Journal, 2022)
The article is devoted to the protection of the rights of women in the Republic of Uzbekistan and the enhancement of their role in society. In addition, priority is given to such issues as discrimination, humiliation, rape of women
Keywords: discrimination; gender; security; Ombudsman, Convention